Pelindungan Hukum Atas Monetisasi Koreografi pada Program Tantangan Menari yang Diunggah Dalam Platform Tiktok - Feliany Kowanda; Miranda Risang Ayu Palar; Laina Rafianti (Universitas Sains dan Teknologi Komputer, 2024)
The understanding of TikTok users tends to be less concerned about someone's creative work. This has led to the widespread practice of TikTok users using choreography creations for monetization on the TikTok platform without the creator's permission. This study aims to determine the legal protection for creators of Dance Challenge choreography regarding monetization on the TikTok platform based on Law Number 28 of 2014 on Copyrights and to determine dispute resolution for choreography owners regarding monetization of Dance Challenge choreography by others without permission on the TikTok platform based on applicable laws and regulations. This research was conducted using the normative juridical and socio-legal approach methods. The research was conducted by conducting both library and field research as the primary research materials. Based on the conducted research, the results show that TikTok users who create and upload choreography works on the TikTok platform automatically receive copyright protection for those choreography works. If a creator feels that their choreographic work has been monetized by others without their permission, the creator can report it through TikTok administration, alternative dispute resolution, arbitration, or legal proceedings.